FINANCIAL LITERACY, LOCUS OF CONTROL AND LOVE OF MONEY IN FINANCIAL MANAGEMENT BEHAVIOR OF KEDIRI MSMES - Kusumawardhany, Sayekti Indah; Hidayah, Islamiati (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
The continuous growth of SMEs has led to increased competition in the business world. In an effort to maintain their business in a competitive environment, SME owners are required to enhance the income they generate. Therefore, financial management behavior plays a crucial role in the success of an SME. Like other regions, SMEs in Kediri have been recovering post-COVID-19 pandemic. Many SMEs have adopted digital technologies to survive and grow. SMEs in Kediri are primarily involved in sectors such as food and beverages, handicrafts, retail trade, and services. This study aims to identify the factors that influence financial management behavior among SMEs in Kediri. The research uses a quantitative approach with a descriptive research design. The population of this study is 400 SMEs, and the sample size is 200 SMEs. The results of this study indicate that the variables of financial literacy, locus of control, and love of money partially influence financial management behavior. Moreover, these variables also have a simultaneous effect on financial management behavior.